2008
DOI: 10.1007/s00299-008-0592-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of SSR markers to determine the anther-derived homozygous lines in coconut

Abstract: Anther culture was used to obtain dihaploid (DH) coconut plants and their ploidy level was determined by flow cytometric analysis. Simple sequence repeat (SSR) marker analysis was conducted to identify the homozygous diploid individuals. Ploidy analysis showed that 50% of the tested plantlets were haploid and 50% were diploid. Polymorphic fragments of the mother palm and their segregation patterns in anther-derived plantlets were used to determine the origin of the diploid plantlets. Using a diagnostic SSR mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
0
25
0
2
Order By: Relevance
“…Formation of callus and embryos was reported from anther coconut explants (Perera et al 2008). Depending on conditions embryos could give rise to new embryos.…”
Section: Anther and Unfertilized Ovary Explantsmentioning
confidence: 98%
See 1 more Smart Citation
“…Formation of callus and embryos was reported from anther coconut explants (Perera et al 2008). Depending on conditions embryos could give rise to new embryos.…”
Section: Anther and Unfertilized Ovary Explantsmentioning
confidence: 98%
“…Depending on conditions embryos could give rise to new embryos. One hundred and twenty-five embryos or calli per 100 anthers were obtained, and 27 % of those were germinated, and 20 plantlets were obtained (Perera et al 2008). They did ploidy analysis showing that one-half of the tested plantlets was haploid and the other half was diploid.…”
Section: Anther and Unfertilized Ovary Explantsmentioning
confidence: 99%
“…Perera et al (2008) also concluded that a single primer pair with the segregating allele in the donor parent is sufficient for distinguishing the population since all the analyzed structures were derived from the same donor parent. SSR markers were also successfully employed in other crops to identify spontaneous dihaploid plants and reveal homozygosity in very early "embryogenesis" (Diao et al 2009;Perera et al 2008;Chani et al 2000;Bouvier et al 2002). Gynogenic plantlets were genetically homozygous, derived from megaspore mother cells and considered spontaneous double haploid melon plants.…”
Section: Identification Of Homozygous Double Haploid Plants By Ssr Anmentioning
confidence: 99%
“…Therefore, these diploid gynogenic plantlets should be investigated for their homozygosity and source of origin before using in breeding programs. Occurrence of spontaneous diploidization is also a common phenomena in other plant species (Cocos nucifera L.: Perera et al 2008;Pyrus communis L.: Bouvier 2002; Cucumis sativus L.: Diao et al 2009;Hui et al 2007). Among these regenerated diploid gynogenic plants, those originating from megaspore mother cell are equivalent to haploids (homozygous) and can be used directly in breeding programs, while those originating from normal somatic cell are heterozygous and would require further inbreeding prior to use as parents (Perera et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation